The effect of contrasting soil textures on the efficiency of alternate wetting-drying to reduce water use and global warming potential - Ariani, Miranti; Hanudin, Eko; Haryono, Eko (Elsevier B.V., 2022)
Alternate wetting-drying (AWD) is known to reduced water use and at the same time also reduced greenhouse gas (GHG) emissions from rice fields. The research aimed at comparing AWD on contrast soil textures. Field experiments were conducted at two sites representing coarse-texture soil (silt loam) and finer-texture soil (silty clay) to study the efficiency of AWD on water use, methane (CH4) and nitrous oxide (N2O) emission, grain yield, global warming potential (GWP), and GHG intensity (GHGI). The experiments were conducted during the 2020 dry season in Central Java province, Indonesia, evaluating continuous flooding (CF) and AWD as the main plot, and biochar-compost (BC) mixture at a rate of 0, 5, and 10 t ha−1as the sub-plot. The results unveiled that AWD on silty clay and silt loam soil reduced water use by 12 and 18, respectively. The implementation of AWD on silt loam soil significantly (p < 0.05) reduced the total GWP by 39.6 without yield loss and GHGI by 38.4 compared to CF. Conversely, on silty clay soil, the GWP and GHGI reduction was marginal (only about 4). Biochar-compost addition was significantly reduced water use in both soil textures. We found that the implementation of AWD on coarse texture is more efficient in reducing water use and GWP. Expanding studies on several rice growing season on multiple location can reduce the limitation of our study and further assist in environmental decision making for the rice system in terms of GHG mitigation action and saving irrigation water. © 2022 Elsevier B.V.